Protective factors of school-going adolescents: A school-based survey in Kerala, South India - U Harikrishnan; Grace Lalhlupuii Sailo (Wolters Kluwer Medknow Publications, 2023)
Introduction: Protective factors such as supportive home and school environments significantly influence the future life outcomes of school-going adolescents. The current study was done to assess the protective factors for home and school of school-going adolescents. Methods: A cross-sectional descriptive survey method was used for with a multistage cluster sampling. Data was gathered from 600 adolescent students enrolled in 19 schools throughout the Kollam district of Kerala. A self-reported validated Indian Adolescent Health Questionnaire was used. Results: Home-related protective factors were found to be significantly correlated with age, sex, and type of school, using a binary logistic regression model. Conclusion: There is a necessity for preparing a strong assessment plan and intervention package for better development of school-going adolescents.